Descriptive Analysis the Analgesic Activity of Chloroform Fraction from Acorus Calamus L. Leaf Extract on Male White Mice (Mus Musculus) Induced by Acetic Acid - Fendy Prasetyawan; Yuneka Saristiana; Ibrahim Fadlannul Haq; Ibrahim Irsyadul Ibad; Ibrahim Iskandar Alfaris (Journal Health of Indonesian, 2024)
Pain management is a critical aspect of pharmaceutical research, and Acorus calamus L., commonly known as jeringau, has garnered attention for its potential analgesic properties. This study focuses on evaluating the analgesic activity of the chloroform fraction from ethanol extract of jeringau leaves (Acorus calamus L.) on male white mice induced by acetic acid. Chronic and acute pain significantly impacts individuals' quality of life, emphasizing the need for effective and safe analgesic alternatives. While Acorus calamus leaf extract has shown pharmacological potential, especially the chloroform fraction, a dedicated investigation into its analgesic effects on animal models is lacking. Male white mice, recognized for their reproducible and measurable responses to painful stimuli, serve as relevant subjects in this study. The population of 25 mice, aged 2-3 months and weighing 20-30 grams, is divided into 5 treatment groups, including negative and positive controls. The study employs three dosages of the chloroform fraction, administered orally, with observations made on writhing behavior following intraperitoneal injection of 0.5% acetic acid. Statistical analysis will evaluate significant differences between treatment groups, providing insights into the analgesic potential. Results indicate that Dosage III (44.8 mg/40g BW) exhibits the highest analgesic efficacy at 73.99%, showcasing a dose-dependent response. The mechanism involves flavonoids inhibiting the cyclooxygenase enzyme, aligning with established analgesic actions. Ibuprofen, the positive control, and jeringau leaf extract demonstrate analgesic effects, reinforcing traditional knowledge. This research contributes to scientific understanding, establishing a foundation for further exploration.